Combustão smouldering : influência da umidade e da configuração do leito no tratamento termoquímico do lodo de esgoto - Abreu, Carlos Eduardo Silva (2015)
The need to search for alternative energy sources that assist in energy generation associated with the thermal processing of any product or rationalized in a sustainable way is a matter of greatimportance. In additionto thisfact, the environmental factor -that after the law disposal of solid waste -becomes an obligatorycondition in the management or deployment of any system or process. Giventhis demand, the SewageSludge (SS) is used in this work in order to conduct an analysis regarding its power generation potential, while suggesting a self-sustaining way of a thermochemical treatment. Therefore, the influence of the material’s moisture and the type configuration of combustionfixed bed(co-current or counter-current) is studiedin this paper. Initially, an analysis of the high heatvalue (HHV) of the sludge as a function of its moisture was performed.The results showed that for a decreaseof the humidity of 20% until the sludge is completely dry, i.e.0%, the HHVincreased from 7487 to 8480 kJ.kg-1, which represents an increase of approximately 14% in SSenergy potential. Then, an analysis of the smoulderingcombustion of sludge counter-current as a function of the moisture was conducted. This analysis showed that the reduction of moisture causes an enhance in the maximum temperature obtained in the process (962 to 1026 ° C), in addition, it also generatedan increase of the combustion frontspeed, from2.43 to 2.99 mm.min-1. Analyses of the cocurrent process showed similar results, such as:the remission of thehumiditycontentelevated the maximum operating temperature and the velocity of propagation of the combustion front. Finally, the results of the process of counter-current and co-currentwere compared, indicating that for the same moisture content, co-current process had higher temperatures and lower velocities of propagation of the combustion front.In parallel to the analysis above, it was verifiedtheinert material content in the sludge comparing the mass of the sample before and after the experiment. All tests showed acontent close to52% of inert matter.